Association of placental manganese levels, maternal gut microbiota, and preeclampsia: a tripartite perspective - Ding, Tianze; Huang, Xiaoli; Ai, Shiwei; Pu, Yudong; Zhao, Wenting; He, Shuzhen; Dang, Yuhui (Frontiers in Microbiology, 2025)
BackgroundPreeclampsia (PE), a leading cause of maternal and fetal morbidity, remains poorly understood mechanistically. While metal elements like manganese (Mn) are critical for placental function, their interplay with gut microbiota in PE pathogenesis is underexplored. This study evaluates placental heavy metal exposure—particularly Mn—and its interaction with gut microbiota in modulating PE risk.MethodsThe study included 21 healthy pregnant women (Control group), and 21 pregnant women diagnosed with PE (PE group). Placental samples were collected to measure metal elements concentrations, while fecal samples were obtained to assess gut microbiota composition. Associations between gut microbiota, PE, and placental Mn levels were analyzed using the Analysis of Composition of Microbiomes with Bias Correction 2 method. Additionally, KEGG pathway enrichment analysis was conducted to identify metabolic pathways linked to PE and Mn levels.ResultsMn levels were significantly lower in the PE group compared to the Control group (p = 0.002). Gut microbiota diversity showed no significant differences between groups, but specific genera were linked to PE and Mn levels: Campylobacter and Porphyromonas were positively correlated with PE and negatively with Mn, while Coprobacillus showed the opposite pattern. KEGG pathway enrichment analysis identified eight metabolic pathways negatively associated with PE and positively linked to Mn, including the degradation of aromatic compounds.ConclusionOur findings suggest that Mn may serve as a protective factor against PE within a certain concentration range. Interactions between Mn and specific bacterial genera (Coprobacillus, Campylobacter, and Porphyromonas) appear to influence PE development by altering gut microbiota metabolic activities. These findings underscore the potential significance of the gut microbiota-Mn interplay in PE pathogenesis.